Future Waste Generation - Forecasts Based on a Macroeconomic Model - Annegrete Bruvoll; Karin Ibenholt (Statistics Norway, Research Department, 1996)
Generation of solid waste is closely associated with the use of tangible factor inputs and production levels in the economy. In this paper, we present projections of waste generated in the Norwegian manufacturing industry based on the development in these factors as simulated by a computable general equilibrium model. Over the simulation period, material input becomes relatively cheaper than labour and energy, thereby making it profitable to substitute materials for other factor inputs. This substitution effect is a general equilibrium effect mainly due to technological change. It dominates the direct material saving impact of technological progress in most production sectors. Thus, generated solid waste rises over the simulation period, both in terms of unit produced and per capita. The analysis predicts an increase in generated waste over the period from 1993 to 2010 in the range of 45 - 110 per cent, depending on the type of waste.
Keywords: D5; Q29; Q39; 330; Solid waste; waste modelling; Norway.